ANALISIS KEMAMPUAN SCIENTIFIC REASIONING SISWA SMP DAN SMA YAYASAN BADAN KARYA KEUSKUPAN SANGGAU - Taek, John kenedi Marcel; Mardiyyaningsih, Asriah Nurdini; Wahyuni, Eko Sri (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
One of the thinking skills is reasoning ability, which includes the process of connecting facts to existing ideas. Each understudy needs great thinking abilities, particularly in the area of SCIENCE so understudies can all the more effectively associate an occasion with the ideas they have learned. The motivation behind this review was to uncover the degree of thinking capacity of the Center and Secondary School Understudies at the Badan Karya Keuskupan Sanggau Establishment. Understudies' thinking skills were estimated utilizing the Lawson Study hall Test Logical Prevailing upon 12 sets of answer-reason things introduced in various decision structure. During the 2021/22 school year, the entire middle and high school population in the Badan Karya Keuskupan Sanggau Foundation's Mathematics and Natural Sciences class served as the research sample. Questions are given online through Google structure. The study revealed that junior and senior high school students in the Badan Karya Keuskupan Sanggau Foundation's Mathematics and Natural Sciences class had reasoning abilities that were still very low on each indicator, falling into the very poor category. The majority of students can only develop concrete reasoning patterns.Key word : Resioning, Lawson's test